Suicide in the military environment - Čabarkapa Milanko M.; Panić Milivoj (Vojnosanitetski Pregled)
Suicide of soldiers has its own specifics, because not only it represents the tragedy for the individuals and their family, but also has great psychological effect on social environment and military unit in which it occurs. Suicide can be caused by variety of factors, as reported in the literature. The case reviewed in this article presents multilateral determination of suicide, with particular stress on the character of each individual and social interaction of soldiers. Psychological complex of basic inferiority, low educational level, family problems, and poor integration into military unit could be considered the leading determinants of this suicide. This emphasizes the importance of certain preventive measures such as more rigorous psychological selection for specific military duty, and the education of non-commissioned officers for better recognition and understanding of pre-suicidal syndrome.